2022
DOI: 10.5812/jssc.121848
|View full text |Cite
|
Sign up to set email alerts
|

Facial Pityriasis Alba, Polymorphous Light Eruption, and Vitiligo in Children: A Dermoscopic Distinction

Abstract: Background: Hypopigmentary skin disorders are the most worrisome complaints from Indian and Indian subcontinent people. Pityriasis alba (PA), polymorphic light eruption (PLE), and vitiligo are clinically look-alike conditions commonly seen in children. Objectives: We attempted to characterize the dermoscopic features of PA and PLE and differentiate them from vitiligo in the facial region in skin of color. Methods: Dermoscopic evaluation was done using a handheld dermoscope at 10X magnification on facial lesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In addition, 30% demonstrated erythema within and surrounding the patches [ 9 ]. In a recent study by Ankad et al, white structureless areas were seen in all of their 30 (100%) patients with Pityriasis alba, with indistinct borders in 86% and fine scales in 70% [ 10 ]. They have also reported that 70% of their patients showed fine brown pigmentation while one patient (3.3%) demonstrated a satellite lesion.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, 30% demonstrated erythema within and surrounding the patches [ 9 ]. In a recent study by Ankad et al, white structureless areas were seen in all of their 30 (100%) patients with Pityriasis alba, with indistinct borders in 86% and fine scales in 70% [ 10 ]. They have also reported that 70% of their patients showed fine brown pigmentation while one patient (3.3%) demonstrated a satellite lesion.…”
Section: Discussionmentioning
confidence: 99%